Social mechanisms behind the poor health of marginalized Roma: Novel insights and implications from four ethnographic studies in Slovakia - Belak, Andrej; van Dijk, Jitse P; Reijneveld, Sijmen A (Social science & medicine (1982), 2024)
Roma represent one of the largest ethnic groups facing marginalization worldwide. However, significant knowledge gaps persist regarding: A) the social mechanisms supporting health-endangering practices among Roma; B) the social mechanisms adversely affecting their use of health services; and C) the social determinants underlying both above pathways. To fill these gaps, we conducted a series of four explorative ethnographic studies spanning over ten years. Beginning in 2004, the series involved 260 participants, including segregated Roma and health services staff in Slovakia. Of the four studies, two addressed gap A, two addressed gap B, and all addressed gap C. Regarding pathway A, we found that Roma in segregated Roma enclaves can be socialized into ethnically framed racialized ideologies that oppose the cultural standards of local non-Roma life, including certain healthy practices. This adherence to counter-cultural ideals of Roma identity increases specific health and care challenges. Regarding pathway B, we discovered that health service frontliners frequently lack any organizational support to better understand and accommodate the current living conditions and practices of segregated Roma, as well as their own and others' racism and professional expectations regarding equity. This lack of support leads many frontliners to become cynical about segregated Roma over their careers, resulting in health services being less effective and exacerbating health problems for both Roma and the frontliners themselves. Concerning pathway C, we found that the societal omnipresence of antigypsyism - racist and racialized anti-Roma ideas and sentiments - serves as a prominent driver of both the above pathways. We conclude that much of the unfavorable health status of Roma can be understood via a systems perspective that embraces structural racism.
Keywords: Anthropology, Cultural; dospělí; Female; Adult; ženské pohlaví; Marginalized Roma; Slovakia; Social Determinants of Health; lidé; kulturní antropologie; Healthcare; Social Marginalization; Discrimination; Male; Romové; Social determinants of health; Racism; sociální marginalizace; rasismus; Roma; Slovenská republika; sociální determinanty zdraví; mužské pohlaví; Ethnic health inequalities; Humans